Aplikasi Pembelajaran Rc (Remote Control) Aeromodelling Untuk Santri Putri Pesantren Islamic Leadership School (Ils) Taruna Panatagama - Setiawan, Ferry; Ardianto, Haris; Marausna, Gaguk; Sehono, Sehono; Jayadi, Arid (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
ILS Panatagama Islamic Boarding School does not yet have sufficient supporting facilities to facilitate learning activities, especially learning in the field of science. Learning facilities are needed to provide insight and prepare students before entering a higher level of education and getting involved with life in the midst of society.The service activity aims to help the application of science learning, especially Physics lessons on RC (Remote Control) Aeromodelling Airplanes at the Taruna Panatagama Putri ILS Islamic Boarding School. The approach method offered to solve partner problems is through observation and discussion with school management, followed by lectures, training workshops and assistance in the use of RC Aeromodelling, especially drones. Through this activity, Santri gain insight and operational strengthening of the use of drones for various activities